Efeito dos anti-inflamatórios não-esteroidais sobre a reabsorção óssea alveolar promovida pelo trauma oclusal primário - Lopes, Ana Cristina Távora de Albuquerque (2015)
The present study aimed to evaluate the effect of the Indomethacin and the Celecoxib anti-inflammatories on the alveolar bone resorption caused by the primary occlusal trauma (OT) experimentally developed in Wistar rats, from the insertion of a unilateral occlusal interference in a lower first molar randomly chosen. Therefore, 55 animals received the treatments during a 14-day period, and were randomly divided in the following groups: Positive Control (PC) (n=15) – OT + distilled water; OT+Indomethacin (n=15); OT+Celecoxib (n=15); Negative Control (NC) (n=10) – No treatment, with the objective of obtaining baseline data. The furcal region of the inferior first molars that underwent occlusal trauma was evaluated through histometry and histochemistry. A morphometric analysis was performed to compare the degree of bone resorption in the labial surface of the first molar, in the area between the cementum-enamel junction and the mesial and distal alveolar bone crest. Histometrically, the inter-group analysis showed greater bone resorption in the OT+Celebra, OT+Indomethacin and PC compared to NC (p<0.0001) groups. There was greater bone resorption in the OT+Celebra group compared to the PC (p=1.524E-05) and OT+Indomethacin (p=0.001064) groups; there was no statistic difference in bone resorption between OT+Indomethacin x PC (p=0.2003). The intergroup histochemical analysis showed a significantly higher number of osteoclasts/mm in the OT+Celecoxib group when compared to NC (p=0.03877). The inter-group morphometric analysis showed no significant difference between the OT+Indomethacin x NC (p=0.1613) groups; however, in the comparison between the two groups, differences between OT+Celecoxib and NC (p=0.04813) and between PC and NC (p=0.01182) were verified. There was a strong positive correlation between the resorption degree and the number of TRAP-positive cells in the PC (r=0.894) and OT+Celecoxib (r=0.933) groups, as well as a low correlation in the NC (r=0.259) and OT+Indomethacin (r=0.234) groups. It could be concluded that the anti-inflammatories utilized did not contribute to bone loss reduction in the OT, considering that the Indomethacin was ineffective and the Celecoxib exacerbated the alveolar bone resorption and the number of osteoclasts resulting from the OT.